2020
DOI: 10.1038/s41598-020-64479-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic analysis of adult ankle fractures using combined Danis-Weber and Lauge-Hansen classification systems

Abstract: This study was to analyze ankle fractures for determining the epidemiology, types, distribution, possible mechanisms and diagnosis precision. Between January 2013 and December 2017, all Chinese patients older than 16 years of age with ankle fractures excluding old ankle fractures and pathological fractures in a tertiary care hospital were analyzed by using the Danis-Weber and Lauge-Hansen classification systems. Among 3952 patients with ankle fractures, 1225 fractures (31%) were Danis-Weber type A, 1640 (42%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…For Weber classification, types A, B, and C in this study accounted for 29%, 51%, and 10%, respectively, similar to those reported in the literature. 11 - 12 In 8% of cases, Weber classification was not possible because there was no fibula fracture. 105 cases were all cases of ankle sprains, of which 97 cases were able to make Lauge-Hansen classification, and eight cases were not able to perform Lauge-Hansen classification.…”
Section: Discussionmentioning
confidence: 99%
“…For Weber classification, types A, B, and C in this study accounted for 29%, 51%, and 10%, respectively, similar to those reported in the literature. 11 - 12 In 8% of cases, Weber classification was not possible because there was no fibula fracture. 105 cases were all cases of ankle sprains, of which 97 cases were able to make Lauge-Hansen classification, and eight cases were not able to perform Lauge-Hansen classification.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, until now a simple, complete, and convincing classi cation for ankle injuries has yet been established. In the literature, combined Weber and Lauge-Hansen classi cations are supported by many orthopedic surgeons [9][10][11]. They believe that the combined classi cations can comprise the majority of ankle injuries related to the malleoli and syndesmosis.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of ankle injuries included motorcycle accident (27 cases), various sports injuries (11 cases), slide (8 cases), fall from stairs (6 cases), and various reasons (11 cases). Fifty-eight injuries were caused by loads from external rotation: 33 supination-external rotation and 25 pronation-external rotation (by Lauge-Hansen classi cation) [9][10][11]. Four cases were associated with type 2 or IIIA open fractures [15].…”
Section: Methodsmentioning
confidence: 99%
“…The causes of ankle injuries included motorcycle accident (27 cases), various sports injuries (11 cases), slide (8 cases), fall from stairs (6 cases), and other causes (11 cases). Fifty-eight injuries were caused by load-bearing during external rotation: 33 supination-external rotation and 25 pronation-external rotation (by Lauge-Hansen classi cation) [9][10][11]. Four cases were associated with type II or IIIA open fractures [15].…”
Section: Methodsmentioning
confidence: 99%
“…Until now, there is no universal classi cation of malleolar fractures with or without SD. In the literature, many orthopedic surgeons have described using the combined Weber and Lauge-Hansen classi cations [9][10][11]. They believe that the combined classi cations may cover the majority of ankle injuries that should not be ignored.…”
Section: Introductionmentioning
confidence: 99%